2018
DOI: 10.1016/j.trci.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of a new photobiomodulation technique against Aβ25–35 peptide–induced toxicity in mice: Novel hypothesis for therapeutic approach of Alzheimer's disease suggested

Abstract: IntroductionPhotobiomodulation was assessed as a novel treatment of Alzheimer’s disease (AD) by the use of a new device RGn500 combining photonic and magnetic emissions in a mouse model of AD.MethodsFollowing the injection of amyloid β 25-35 peptide in male Swiss mice, RGn500 was applied once a day for 7 days either on the top of the head or the center of abdomen or both.ResultsRGn500 daily application for 10 min produced a neuroprotective effect on the neurotoxic effects of amyloid β 25-35 peptide injection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 54 publications
(104 reference statements)
2
47
0
Order By: Relevance
“…The use of tPBM significantly reduced the Aβ plaques, and improved spatial memory and behavioral and motor skills in treated animals on day 21. Blivet et al [148] used male Swiss mice and also injected Aβ 25-35 peptide into the hippocampus. tPBM used a RGn500 device that emitted 850 nm laser and LED and 625 nm LED all pulsed at 10 Hz and surrounded with a ring-shaped magnet creating a 200 mT static magnetic field.…”
Section: Tpbm For Ad In Animal Modelsmentioning
confidence: 99%
“…The use of tPBM significantly reduced the Aβ plaques, and improved spatial memory and behavioral and motor skills in treated animals on day 21. Blivet et al [148] used male Swiss mice and also injected Aβ 25-35 peptide into the hippocampus. tPBM used a RGn500 device that emitted 850 nm laser and LED and 625 nm LED all pulsed at 10 Hz and surrounded with a ring-shaped magnet creating a 200 mT static magnetic field.…”
Section: Tpbm For Ad In Animal Modelsmentioning
confidence: 99%
“…The wavelength was again shown to be an important parameter, with NIR wavelengths showing a more pronounced effect than red light, and the proportion of bacteria associated with a healthy microbiome in mice generally increased while the proportion of bacteria associated with a dysregulated microbiome generally decreased. Blivet and colleagues have also hypothesized that the microbiome (in mice) is important for the treatment of Alzheimer's disease with PBM 154 and have shown significant changes in the microbiome of mice injected with b-amyloid after treatment with a combination of PBM wavelengths and a static magnetic field (personal communication and 155 ). Recent preliminary work from our laboratory (unpublished) has also indicated that changes in the human (quasimetabolic syndrome) microbiome occur after treatment with PBM, including increases in Akkermansia muciniphila, Bifidobacterium sp., and Faecalibacterium sp., all recognized as correlated with a healthy microbiome, [156][157][158] and decreases in the Firmicutes:Bacteroides ratio, proposed as an indicator of gut health.…”
Section: Pbm Alters the Microbiomementioning
confidence: 99%
“…For example, a human study with a 10-Hz pulse frequency was recently published, 57 and several preclinical studies explored treatment outcomes of pulsed tPBM on different types of neurological conditions with different pulse frequencies. [58][59][60][61][62] Table 4 lists corresponding pulsed frequencies, studied species, and related references. In principle, one advantage of CW tPBM is to deliver more optical energy/ fluence, and thus more dosage in a given time, but one disadvantage is to possibly create more heat on the skin surface.…”
Section: Continuous-wave Versus Pulsed Tpbmmentioning
confidence: 99%